Four-dimensional in vivo X-ray microscopy with projection-guided gating - Mokso, Rajmund (Sci Rep, 2015)
Visualizing fast micrometer scale internal movements of small animals is a key challenge for functional anatomy, physiology and biomechanics. We combine phase contrast tomographic microscopy (down to 3.3 μm voxel size) with retrospective, projection-based gating (in the order of hundreds of microseconds) to improve the spatiotemporal resolution by an order of magnitude over previous studies. We demonstrate our method by visualizing 20 three-dimensional snapshots through the 150 Hz oscillations of the blowfly flight motor.